Effectiveness of the didactic project "Between university and employment" - Mariusz Pyra; Marek Kuźmicki (Rozprawy Społeczne)
Abstract The aim is to determine the effectiveness of the teaching activities carried out as part of the teaching project. The conducted research shows a significant improvement in the competence level indicator.